Conceptual framework for the study of food waste generation and prevention in the hospitality sector. (March 2016) - Papargyropoulou, Effie; Wright, Nigel; Lozano, Rodrigo; Steinberger, Julia; Padfield, Rory; Ujang, Zaini
Highlights: A conceptual framework for studying food waste generation and prevention is proposed. Biophysical flows of food waste are linked to economic values and social practices. Methods from ethnography and grounded theory are used in research design. Material and economic flow analysis is carried out for incoming food and food waste. Eco-efficiency analysis of food items is carried out. Abstract: Food waste has significant detrimental economic, environmental and social impacts. The magnitude and complexity of the global food waste problem has brought it to the forefront of the environmental agenda; however, there has been little research on the patterns and drivers of food waste generation, especially outside the household. This is partially due to weaknesses in the methodological approaches used to understand such a complex problem. This paper proposes a novel conceptual framework to identify and explain the patterns and drivers of food waste generation in the hospitality sector, with the aim of identifying food waste prevention measures. This conceptual framework integrates data collection and analysis methods from ethnography and grounded theory, complemented with concepts and tools from industrial ecology for the analysis of quantitative data. A case study of food waste generation at a hotel restaurant in Malaysia is used as an example to illustrate how this conceptual framework can be applied. The conceptual framework links the biophysical and economic flows of food provisioning and waste generation, with the social and cultural practices associated with food preparation and consumption. The case study demonstrates that food waste is intrinsically linked to the way we provision and consume food, the material and socio-cultural context of food consumption and food waste generation. Food provisioning, food consumption and food waste generation should be studied together in order to fully understand how, where and most importantly why food waste is generated. This understanding will then enable to draw detailed, case specific food waste prevention plans addressing the material and socio-economic aspects of food waste generation.